Pengembangan Usaha Pertanian Melalui Pelatihan Pemasaran Dan Produksi Olahan Hasil Panen Menjadi Stik - Alfian Djafar; Doddy Suanggana; Gad Gunawan; Agung Prabowo; Achmad Farizul Hasmi; Felita Tsany Pandya; Tina Febriana; Muhammad Syaiful Umara; Maulana Bayu Iqmal; Rukayya Syakira; Naufal Akmal; Muhammad Irwan Gunawan (CV. Multi Kreasi Media, 2023)
Business opportunities in the agricultural sector have great potential, especially in processing harvests into value-added products. The potential for developing processed harvest products in Balikpapan is substantial, given its role as a primary producer of secondary crops used as the main raw materials. Therefore, the Kalimantan Institute of Technology seeks to contribute to the development of community welfare, especially in Balikpapan. The method used is identifying problems and finding solutions. The main problem faced by the Swa Tani Farmers group is the direct sale of their harvests to the collector or through safekeeping at nearby kiosks. The production of harvest-derived products is a part-time endeavor, with sales exclusively conducted through kiosks or WhatsApp (WA) groups. Community service activities have been implemented to foster an entrepreneurial spirit by encouraging creativity and innovation. The innovations carried out are in the form of developing processed harvest products and also management innovations in the marketing sector. Marketing training contains material to provide an in-depth understanding of the importance of marketing strategies, as well as simple but effective marketing methods. The practiced harvest product is in the form of sticks, with the primary raw materials for stick production being cassava, taro, and bananas. Evaluation of the results of processed products shows that cassava sticks dominate in consumer choice, while taro sticks require further adjustments, and banana sticks need additional flavor aspects.